Essential role of pre-existing humoral immunity in TLR9-mediated type I IFN response to recombinant AAV vectors in human whole blood - Alakhras, Nada S.; Moreland, Christopher A.; Wong, Li Chin; Raut, Priyam; Kamalakaran, Sid; Wen, Yi; Siegel, Robert W.; Malherbe, Laurent P. (Frontiers in Immunology, 2024)
Recombinant adeno-associated virus (AAV) vectors have emerged as the preferred platform for gene therapy of rare human diseases. Despite the clinical promise, host immune responses to AAV vectors and transgene remain a major barrier to the development of successful AAV-based human gene therapies. Here, we assessed the human innate immune response to AAV9, the preferred serotype for AAV-mediated gene therapy of the CNS. We showed that AAV9 induced type I interferon (IFN) and IL-6 responses in human blood from healthy donors. This innate response was replicated with AAV6, required full viral particles, but was not observed in every donor. Depleting CpG motifs from the AAV transgene or inhibiting TLR9 signaling reduced type I IFN response to AAV9 in responding donors, highlighting the importance of TLR9-mediated DNA sensing for the innate response to AAV9. Remarkably, we further demonstrated that only seropositive donors with preexisting antibodies to AAV9 capsid mounted an innate immune response to AAV9 in human whole blood and that anti-AAV9 antibodies were necessary and sufficient to promote type I IFN release and plasmacytoid dendritic (pDC) cell activation in response to AAV9. Thus, our study reveals a previously unidentified requirement for AAV preexisting antibodies for TLR9-mediated type I IFN response to AAV9 in human blood.